1992
DOI: 10.1017/s0022215100118900
|View full text |Cite
|
Sign up to set email alerts
|

Branchial cleft and pouch anomalies

Abstract: We present a retrospective study of 106 patients with branchial cleft and pouch anomalies who presented to the Hospital for Sick Children between 1948 and 1990. The relevant embryology of the branchial apparatus is summarized and a theoretical description of individual anomalies given.Second branchial cleft sinuses were the most common anomalies, and the majority were managed simply, with adequate excision and a low recurrence rate. Five cases of first branchial cleft anomalies are presented, emphasizing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
221
4
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(233 citation statements)
references
References 13 publications
5
221
4
3
Order By: Relevance
“…They represent 90-95% of branchial anomalies. 4 During embryonic development, the second arch grows caudally and it covers the second, third, and fourth branchial clefts. The cervical sinus of His is formed by the fusion of this second arch with the enlarging epipericardial ridge of the fifth arch.…”
Section: Discussionmentioning
confidence: 99%
“…They represent 90-95% of branchial anomalies. 4 During embryonic development, the second arch grows caudally and it covers the second, third, and fourth branchial clefts. The cervical sinus of His is formed by the fusion of this second arch with the enlarging epipericardial ridge of the fifth arch.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 Most branchial arch anomalies arise from the second branchial cleft (92.45%). 1,8 Anomalies of first arch remnants (4.72%), third (1.87%) and fourth arch anomalies (0.94%) are quite rare [d]. Bajaj et al, have reported a higher incidence of second branchial anomalies (78%) in their series of 80 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Typically a 4th branchial pouch sinus presents in the 1st decade of life as recurrent neck abscesses often involving the perithyroid space, recurrent suppurative thyroiditis [4][5][6][7] which may even require a hemithyroidectomy [8], recurrent pseudothyroiditis [9], retro pharyngeal abscess with recurrent cellulitis [10] which may extend to the mediastinum to form an abscess there [11], neonatal or pediatric respiratory distress with [12,2] stridor or even as an asymptomatic mass [12] or as an incidental radiological fi nding [12]. This condition is often misdiagnosed initially until recurrence of symptoms leads to further investigations and a defi nitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Identifi cation of the tract can be facilitated by cannulation and injection of methylene blue endoscopically with a cannula [2,15] or by introduction of a Fogarty ® embolectomy catheter. Other treatment modalities have also been described like laser coagulation by endoscopy [16], chemocautery with TCA [17] and endoscopic fi brin sealing [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation